Cordycepin attenuates NLRP3/Caspase-1/GSDMD-mediated LPS-induced macrophage pyroptosis - Liu, Zige; Lv, Li; Wei, Jiao; Xie, Yuli; Jili, Mujia; Huang, Yian; Yang, Rirong; Luo, Yu (Frontiers in Pharmacology, 2025)
Pyroptosis, a form of programmed cell death driven by the NLRP3 inflammasome, is a key contributor to inflammation in various diseases. This study aimed to investigate the anti-inflammatory mechanisms of cordycepin, focusing on its role in macrophage pyroptosis. Molecular docking analysis was performed to evaluate the binding affinity of cordycepin to key pyroptosis-related proteins, including NLRP3, Caspase-1, and GSDMD. RAW264.7 cells were pre-treated with cordycepin to assess its effects on pyroptosis. Key measurements included reactive oxygen species (ROS) levels, xanthine oxidase (XO) activity, and the expression of NLRP3, Caspase-1, and GSDMD. Additionally, lactate dehydrogenase (LDH) release, interleukin (IL)-1β and IL-18 levels in the culture supernatant, and macrophage cell death rates were evaluated using Hoechst 33342/PI dual staining. The results demonstrated that cordycepin exhibits strong binding affinity for NLRP3, Caspase-1, and GSDMD. Cordycepin pre-treatment significantly reduced ROS levels and XO activity, inhibited the expression of NLRP3, cleaved-Caspase-1, and cleaved-GSDMD, and decreased pyroptosis-associated inflammatory cytokines IL-1β and IL-18, along with Caspase-1 activity. Furthermore, cordycepin reduced the macrophage pyroptosis rate. In conclusion, cordycepin inhibits macrophage pyroptosis by reducing XO activity, suppressing ROS production, and regulating the expression of key molecules in the NLRP3/Caspase-1/GSDMD pathway. These findings provide a strong experimental basis for the potential development of cordycepin as a novel anti-inflammatory agent.